Post-mortem interval comparison in different meat conditions - Mohamad, Durratun Nasuha (2022)
Lack of data in different post-mortem interval estimation conditions limit the application of entomological evidence in crime investigation. Therefore, this study investigates the decomposition stages, insect succession patterns, complete life cycle of fly and larva consumption in fresh meat, frozen meat, dry fresh and dry frozen meat. There are 5 decomposition stages for the fresh and frozen meat : fresh, fresh decay, advance decay, post decay and dry whereas 3 decomposition stages for the dry fresh and dry frozen meat were dry, dry decay and remains. The duration for the fly to complete their life cycle is within 13 days at an average ambient temperature of 28.80 ⁰C with relative humidity of 76.50%. Six necrophagous fly species, beetles with several ants were observed in both decomposed fresh meat and frozen meat but only ants were observed in both dry meat. For larva consumption in each of the meat conditions, the average meat consumed per larvae was 0.68 g in fresh meat, 0.67 g in frozen meat, 0.54 g in dry fresh meat and 0.47 g in dry frozen meat. These decomposition stages, insect successions patterns, the complete life cycle of the fly and larva consumption information deserve consideration as it provides valuable baseline data for post-mortem interval estimation related to different conditions of the dead body found in shaded areas in any forensic entomology cases specifically in Kelantan.